SOME ISSUES TO THE HISTORY OF COPYRIGHT LAW IN UKRAINE - Shust, Nataliia B.; Smorodyna, Alla E. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
Purpose: review and analyze the ways of acknowledgment and establishment of moral and economic rights of intellectual property under the Soviet copyright law until such rights have been implemented in the Civil Code of Ukraine dated 2003. Methods: optimization of enforcement of the provisions of the Civil Code of Ukraine, provided for moral and economic rights of intellectual property under the Soviet copyright law until such rights have been implemented in the Civil Code of Ukraine. Results: the Civil Code of Ukraine has restructured the system of the intellectual property rights in Ukraine and introduced the general provisions that apply to all objects of the intellectual property right. Discussion: regulations of USSR and Ukrainian SSR on civil laws and copyright, Ukrainian legislation on copyright.